(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This study examines the effectiveness of using internet memes as a contextual tool for teaching the English subjunctive mood to secondary school students. Addressing the common issue of low student engagement in traditional grammar instruction, the research proposes a «meme-to-rule» model that connects formal grammar with students’ digital reality. An experimental lesson involving tenth-graders demonstrated that this approach significantly increases learner motivation and facilitates a more profound initial understanding of the subjunctive’s semantic functions (e.g., expressing wishes, hypothetical situations) compared to a standard rule-first presentation. The findings advocate for the strategic integration of culturally relevant digital content to make grammar instruction more engaging and meaningful.